2018
DOI: 10.1371/journal.pone.0206840
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome among medical residents: A systematic review and meta-analysis

Abstract: BackgroundBurnout is a psychological syndrome that is very common among medical residents. It consists of emotional exhaustion (EE), depersonalization (DP) and reduced personal accomplishment (PA).ObjectiveTo estimate burnout among different medical residency specialties.MethodsA systematic review with meta-analysis was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A search of bibliographic databases and grey literature was conducted, from incep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
265
8
44

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(403 citation statements)
references
References 57 publications
22
265
8
44
Order By: Relevance
“…Third, healthcare providers have reported experiencing various mental health problems, including emotional exhaustion, which may result in suboptimal performance in workplaces, as found in this umbrella review. Several evidence-based reviews have reported a high burden of professional burnout among healthcare providers [44][45][46], which may exacerbate during quarantine and isolation for infection prevention. Such evidence suggests academic and professional approaches to sensitize the clinical students and healthcare providers to be aware of such issues in practical settings and adopt protective mental health measures before working in such stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Third, healthcare providers have reported experiencing various mental health problems, including emotional exhaustion, which may result in suboptimal performance in workplaces, as found in this umbrella review. Several evidence-based reviews have reported a high burden of professional burnout among healthcare providers [44][45][46], which may exacerbate during quarantine and isolation for infection prevention. Such evidence suggests academic and professional approaches to sensitize the clinical students and healthcare providers to be aware of such issues in practical settings and adopt protective mental health measures before working in such stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…including emotional exhaustion, which may result in suboptimal performance in workplaces, as found in this umbrella review. Several evidence-based reviews have reported a high burden of professional burnout among healthcare providers [50][51][52], which may exacerbate during quarantine and isolation for infection prevention. Such evidence suggests academic and professional approaches to sensitize the clinical students and healthcare providers to be aware of such issues in practical settings and adopt protective mental health measures before working in such stressful conditions.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…Actitudes deficientes en autocuidado se encuentran en el corazón de la cultura médica. Existe amplia evidencia que el estrés crónico y burnout (entendido como un síndrome de agotamiento físico y mental relacionado con la vida laboral) 49 , acompañan a la profesión médica desde el pregrado [50][51][52][53] . Es posible identificar múltiples factores explican el mantenimiento de estrés y burnout entre los médicos.…”
Section: Estrés Y Burnoutunclassified